Human Resources Readiness Assessment in The Framework of Business Development - Tinneke Evie Meggy Sumual; Grace J. Soputan; Arie F. Kawulur (AIBPM Publisher, 2020)
This paper aims to describe the readiness of human resources in the context of business development in the business of “Tibo-tibo” women fishermen in North Minahasa, Indonesia. Descriptive qualitative research methods were used to analysis valuable data and information. Data collected with observation, questionnaires and in-depth interviews technique. The results showed that human resources are very supportive of doing business development as seen from the experience business as a fish seller, productive age, and motivation to work and family support as a fisherwoman. The results of subsequent studies are human resources challenging to identify traditional work behaviour, shortterm work habit, lack of creativity on product and marketing innovation and also the habit on making loan in high interest. This research recommends human capital and social capital empowering to increase local potential.